The biosecurity benefits of genetic engineering attribution - Gregory Lewis (Nature Portfolio, 2020)
A key security challenge with biosecurity threats is determining the responsible actor. In this Perspective, the authors review recent developments in using genetic sequence to assign a lab-of-origin and the potential protection it provides against misuse of synthetic biology.